The right of acquisition : options in commercial real estate - Furfine, Craig; Petersen, Mitchell A. ([London] : SAGE, 2016)
In April 2012 Bill Nichols, a financial analyst at the real estate investment firm Koenig Capital, was about to enter a unique lease renegotiation. One of Koenig's tenants, Hasperat Inc., had sixteen years left on its long-term lease of the Kelley Building, a 165,000-square-foot office building in downtown Cleveland. The lease contained a clause giving Hasperat the option to buy the Kelley Building from Koenig. This study details what then happened when Nichols tried to place a mortgage on the property.
Originally Published in: Furfine, C., & Petersen, M. (2014). The Right of Acquisition: Options in Commercial Real Estate. 5-114-001. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Commercial real estate -- Case studies